At-Risk Drinking Is Independently Associated With Acute Kidney Injury in Critically Ill Patients. Issue 8 (August 2019) - Gacouin, Arnaud; Lesouhaitier, Mathieu; Frerou, Aurelien; Painvin, Benoit; Reizine, Florian; Rafi, Sonia; Maamar, Adel; Le Tulzo, Yves; Tadié, Jean Marc
Abstract : Objectives: Unhealthy use of alcohol and acute kidney injury are major public health problems, but little is known about the impact of excessive alcohol consumption on kidney function in critically ill patients. We aimed to determine whether at-risk drinking is independently associated with acute kidney injury in the ICU and at ICU discharge. Design: Prospective observational cohort study. Setting: A 21-bed polyvalent ICU in a university hospital. Patients: A total of 1, 107 adult patients admitted over a 30-month period who had an ICU stay of greater than or equal to 3 days and in whom alcohol consumption could be assessed. Interventions: None. Measurements and Main Results: We assessed Kidney Disease Improving Global Outcomes stages 2–3 acute kidney injury in 320 at-risk drinkers (29%) and 787 non–at-risk drinkers (71%) at admission to the ICU, within 4 days after admission and at ICU discharge. The proportion of patients with stages 2–3 acute kidney injury at admission to the ICU (42.5% vs 18%; p < 0.0001) was significantly higher in at-risk drinkers than in non–at-risk drinkers. Within 4 days and after adjustment on susceptible and predisposing factors for acute kidney injury was performed, at-risk drinking was significantly associated with acute kidney injury for the entire population (odds ratio, 2.15; 1.60–2.89; p < 0.0001) in the subgroup of 832 patients without stages 2–3 acute kidney injury at admission to the ICU (odds ratio, 1.44; 1.02–2.02; p = 0.04) and in the subgroup of 971 patients without known chronic kidney disease (odds ratio, 1.92; 1.41–2.61; p < 0.0001). Among survivors, 22% of at-risk drinkers and 9% of non–at-risk drinkers were discharged with stages 2–3 acute kidney injury ( p < 0.001). Conclusions: Our results suggest that chronic and current alcohol misuse in critically ill patients is associated with kidney dysfunction. The systematic and accurate identification of patients with alcohol misuse may allow for the prevention of acute kidney injury. Abstract : Supplemental Digital Content is available in the text.